Avaliação da modificação das condições operacionais no comportamento do primeiro estágio do sistema francês de wetlands construídos - Camila Maria Trein (2020)
This research, aimed to contribute to a better understanding of the performance in terms of treatment of the first stage of the vertical constructed wetland - French System (VCW-FS) operating in warmer climatic conditions than in France. The investigated system was located at the Centre for Research and Training in Sanitation (CePTS - UFMG / COPASA), Belo Horizonte/Minas Gerais. During the monitoring period, the system operated with a reduced area (total 0.6 m2 .p.e-1 ). With only two units in parallel, the characterization of the units was influenced by the organic deposit layer on the surface, with unit I working with the accumulated sludge since the beginning of the system's operation (average height < 10 cm), and unit II had lower sludge height (average < 5 cm), due to its removal before the beginning of the research. Receiving 24 pulses.day-1 , the units operated with extended feeding time, with seven days of feeding and seven days of rest. Searched evaluate the operation of the units in three sequential steps: 1) with unsaturated medium (22 months of operation), 2) with saturated bottom and interconnected with the unit next to it (over 11 months of operation) and 3) with saturated bottom, without interconnection (total of 4 months of operation). The rate of sludge accumulation in the two units was less than 1 cm.year-1 , lower than the values found in systems operated in regions of temperate climate (1.5 to 3.0 cm.year-1 ) with three units in operation (1.2 m2 .p.e-1 total). The classification of the units as mature (organic matter < 60%, thermal index > 0.80 and humification index > 1.0) was obtained even with the different sludge accumulation times (units I and II with less than 10 and 3 years, respectively). Under prevailing aerobic conditions in the units with unsaturated medium (step 1), the effluent was within the least stringent discharge standards (average COD removal efficiencies of 61 - 72%, TSS of 85 - 81% and TKN of 59 - 60 %, respectively for units I and II). With the data of physicalchemical monitoring, in conditions of unsaturated medium it was possible to find values that support the operation of the units with extended feeding cycle (seven days instead of three and a half days, according to French recommendations), aiming to reduce the operational. The production of NO3 - -N in both units was higher in the first pulse, decreasing progressively as the feeding period progressed, coinciding with the oxygen concentration in the units' effluent. The system configuration with the saturated and interconnected bottom (step 2) allowed for average removal efficiencies of organic matter of COD and TSS of 79 and 89%, respectively for unit I and, 74 and 91% respectively for unit II, and nitrogen of 53 and 41% for TN in unit I and II, respectively. With simpler operating conditions, the results of monitoring the units with the saturated bottom, without interconnection (step 3) were better in terms of TKN and NH4 + -N (65 and 58%, respectively for unit I; 70 and 55 %, respectively for unit II). In this last configuration, the TN removal efficiencies were 30 and 29% for units I and II, respectively. Thus, through the results of the physical-chemical parameters it was possible to verify that the potential for nitrification and denitrification was sensitive to the proposed operational conditions (throughout the feeding cycle and in conditions with unsaturated medium and saturated bottom, with or without interconnection) of VCW-FS. In general, the results showed that, even with the various differences in terms of design, hydraulic and organic loading rates, as well as sludge accumulation rates, the treatment performance and the organic fraction characteristic of the organic layer surface layer in systems with reduced area adapted to the Brazilian reality they were quite similar to the French.